2015
DOI: 10.3329/jesnr.v7i2.22217
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Pattern of Land Use Change in Dhaka City Using Remote Sensing and GIS Application

Abstract: This study assessed the extent and trend of landuse/cover change in three selected area of Dhaka city, Bangladesh. This paper examined the use of GIS and Remote Sensing in mapping Land Use/Land Cover in Dhaka city of Landsat imageries of 1960, 2000 and 2014 were downloaded from the Landsat website and to detect the changes that has taken place in this status between these periods. Remote sensing and GIS based software (ILWIS) were used to produce and analysis the land use maps and least square method was funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…Griffiths et al (2010) also showed that agricultural land decreased to 73.7% between 1990 and 2006 in Dhaka city. Overall, agricultural land decreased 39.94% between 1960 and 2014 in Dhaka city [33]. On the basis of existing spatial studies, the Markov chain model based analysis estimated that the agricultural land conversion to built-up by 26% between 2008 and 2020 in the city [39].…”
Section: Agricultural Landmentioning
confidence: 99%
See 4 more Smart Citations
“…Griffiths et al (2010) also showed that agricultural land decreased to 73.7% between 1990 and 2006 in Dhaka city. Overall, agricultural land decreased 39.94% between 1960 and 2014 in Dhaka city [33]. On the basis of existing spatial studies, the Markov chain model based analysis estimated that the agricultural land conversion to built-up by 26% between 2008 and 2020 in the city [39].…”
Section: Agricultural Landmentioning
confidence: 99%
“…The Location Quotient method based study estimated that vegetation decreased 66% between 1960 and 2014 [33]. Similarly, the Maximum Value Composite (MVC) technique calculated a loss of 66.87 km 2 area between 1989 and 2009 [82].…”
Section: Forest Covermentioning
confidence: 99%
See 3 more Smart Citations